Rational Consumption And Islamic Ethics: Monzer Kahf's Perspective In Understanding Digital Product Consumption Patterns - Royhan Rangkuti, Mhd; Batubara, Sarmiana (Proceedings of International Conference on Islamic Economic Finance and Social Finance (ISSN: XXXX-XXXX) (ESSN: XXXX-XXXX), 2025)
This research examines the concept of rational consumption and Islamic ethics in Monzer Kahf's perspective, especially in understanding the consumption patterns of digital products. In the context of growing digitalization, the consumption of digital products is an inevitable phenomenon, but it needs to be based on Islamic principles. Kahf emphasizes the importance of balance between material needs and spiritual values, as well as the principles of halal and thayyib in every aspect of life, including digital consumption. This research uses a qualitative approach with descriptive analysis, referring to primary sources such as the Qur'an and Hadith, as well as relevant secondary data. The results show that consumption patterns of digital products in Islam must follow the principle of rationality, avoid excessive consumptive behavior, and emphasize social responsibility through the concept of zakat and philanthropy. Kahf's thinking provides a strong basis in formulating consumption ethics in accordance with Islamic guidance, as well as presenting relevant solutions for modern societies that are increasingly connected to the digital world.